2021
DOI: 10.1002/jbm.b.34993
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of hydrogels for repair of traumatic spinal cord injuries: A systematic review and meta‐analysis

Abstract: Hydrogels have been used as promising biomaterials for regeneration and control of pathophysiological events after traumatic spinal cord injuries (TSCI). However, no systematic comparison was conducted to show the effect of hydrogels on pathophysiological events. This study was designed to address this issue and evaluate the regenerative potential of hydrogels after TSCI. From 2857 records found in MEDLINE and EMBASE databases (April 23, 2021), 49 articles were included based on our inclusion/exclusion criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 65 publications
(693 reference statements)
0
1
0
Order By: Relevance
“…Several novel treatments have shown promise in ameliorating SCI sequelae. One of these is hydrogels, an analog of the extracellular matrix of a soft tissue [59].…”
Section: Clinical Phase Treatmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Several novel treatments have shown promise in ameliorating SCI sequelae. One of these is hydrogels, an analog of the extracellular matrix of a soft tissue [59].…”
Section: Clinical Phase Treatmentmentioning
confidence: 99%
“…In their systematic review and meta-analysis of animal models, Ayar et al [59] found notable improvements in the pathophysiological outcomes of SCI after treatment with hydrogels. One such finding includes the potential of hydrogels to improve motor function after SC.…”
Section: Clinical Phase Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…A widely used strategy is to locally reconstruct a permissive environment for neural regeneration with biomaterials, which can provide physical and biochemical cues to axonal growth. As a three-dimensional (3D) aqueous matrix, hydrogel has been regarded as an appealing option that can simulate the complex structure of ECM and serve as a bridge to promote neural regeneration ( 3 ).…”
Section: Introductionmentioning
confidence: 99%